Justice and constitutional and legal bases of civil proceedings in the countries of Commonwealth of independent states (Journal of actual problems of jurisprudence, 2018)
Some questions on constitutional-law bases of civil proceeding of Community of Independent States are considered in this article. In the Commonwealth countries of the independent states there are general regularities of development as the states. It is connected with the historical legal and geopolitical reasons. The countries which are a part of the commonwealth are connected not only history, also connected by the legal, economic, social reasons. These situations define the main tendencies of development of legal system of the CIS countries now.Key words: CIS countries, civil legal proceedings, constitutional and legal bases, legal system.